PEMENTORAN DALAM PROGRAM PEMBANGUNAN GURU BAHARU KEMENTERIAN PENDIDIKAN MALAYSIA (Mentoring In the New Teacher Development Program by the Ministry Of Education Malaysia) - Marjonet, Juairiah; Abu Bakar Ah, Siti Hajar; Omar, Noralina (The Malaysian Journal of Social Administration, 2020)
This article evaluates a mentoring program for new teachers, namely the New Teacher Development Program (PPGB). The PPGB mentoring program is a school-based structured guidance program designed for professional development, knowledge enhancement, and teachers' upskilling in line with the teaching values set in the Malaysian Teacher Standards (SGM). The study was conducted using the Kirkpatric Four-Level Assessment Model, which focused on a new teacher's reaction, knowledge, behavior, and outcome (competencies). The cross-sectional survey was administered to 390 new teachers in six zones throughout Malaysia. Primary data was collected using a set of structured questionnaires. Descriptive statistics are used to measure the level of all constructs. The findings show that the level of PPGB achievement is high in terms of mentoring. There is no significant difference between teacher competencies based on location due to PPGB factors that have been well established and successfully adapted by new teachers. However, there are still some significant element which shows differences in terms of program achievement level.